2004
DOI: 10.1111/j.1550-7408.2004.tb00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Vorticetta microstoma Stalk Formation by Wheat Germ Agglutinin

Abstract: Fluorescently labeled conjugates of wheat germ agglutinin and concanavalin A stained the contractile stalk but not the cell body of Vorticella microstoma trophonts. Binding of the fluorescent conjugants did not noticeably alter the activity of the trophonts. However, unconjugated wheat germ agglutinin prevented free swimming telotrochs from adhering to a glass surface and deploying a contractile stalk during differentiation into trophonts. These observations indicated that the stalk, the material that binds th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Although swimming Vorticella cells could be utilized similarly to C. reinhardtii and P. caudatum , the swimming of stalkless Vorticella has been rarely studied. If swimming Vorticellae are to be used, furthermore, their stalk formation will need to be inhibited [ 160 ].…”
Section: Discussion and Future Outlookmentioning
confidence: 99%
“…Although swimming Vorticella cells could be utilized similarly to C. reinhardtii and P. caudatum , the swimming of stalkless Vorticella has been rarely studied. If swimming Vorticellae are to be used, furthermore, their stalk formation will need to be inhibited [ 160 ].…”
Section: Discussion and Future Outlookmentioning
confidence: 99%
“…V. microstoma is a very resistant protist recognised for taking up heavy metals such as lead, cadmium, copper, nickel and mercury ions [226,227]. It also forms stalks after their free-swimming stage, however, Bramucci and Nagarajan [228] showed that in presence of inhibitors they could stay in such stage. Interestingly, activated sludge was more favourable for V. microstoma at both WWTPs (3.2% in Garmerwolde and 1.2% in Vroomshoop) than granular sludge (< 1% in all the samples).…”
Section: Discussionmentioning
confidence: 99%
“…Typically it takes several hours. The chemical composition of the adhesive pad is not yet fully known [4], and a non-invasive method for detaching Vorticella has not been established, although mechanical detachment methods have been demonstrated [5,6]. One such method involves shaking a flask containing Vorticella, which loosens the attached cells and prevents them from adhering to the surface [5].…”
Section: Introductionmentioning
confidence: 99%